2010
DOI: 10.1074/jbc.m110.113332
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Accessibility of Cytoplasmic Substances to the Pore Associated with Activation of the Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel

Abstract: One logical interpretation of these findings is that cytoplasmic access to residues at the narrowest region of the pore changes concomitant with activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
142
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(165 citation statements)
references
References 59 publications
19
142
3
1
Order By: Relevance
“…These results confirmed that TM6 residues line the pore and strongly supported the proposed narrowing near position 338 from the extracellular end of the pore (Linsdell et al 2000;McCarty and Zhang 2001). On the other hand, applying bulky MTS reagents from the cytoplasmic side of the channel identified position 341 as the accessibility limit (Bai et al 2010;El Hiani and Linsdell 2010). Thus, it appears that the pore is constructed with two fairly accessible internal and external vestibules with a "bottleneck" that traverses only one helical turn (Norimatsu et al 2012).…”
Section: Pore-lining Tmssupporting
confidence: 72%
See 1 more Smart Citation
“…These results confirmed that TM6 residues line the pore and strongly supported the proposed narrowing near position 338 from the extracellular end of the pore (Linsdell et al 2000;McCarty and Zhang 2001). On the other hand, applying bulky MTS reagents from the cytoplasmic side of the channel identified position 341 as the accessibility limit (Bai et al 2010;El Hiani and Linsdell 2010). Thus, it appears that the pore is constructed with two fairly accessible internal and external vestibules with a "bottleneck" that traverses only one helical turn (Norimatsu et al 2012).…”
Section: Pore-lining Tmssupporting
confidence: 72%
“…Linsdell et al (2000) first reported that mutations at residues F337 and T338 in TM6 strongly affected the permeability sequence. Those findings were extended by testing additional TM6 mutants Ge et al 2004) and by using cysteine scanning to explore the accessibility of TM6 residues (Alexander et al 2009;Bai et al 2010;El Hiani and Linsdell 2010). Alexander et al (2009) compared the effects of two types of reactive compounds on a series of TM6 cysteine mutants: large methanethiosulfonate (MTS) compounds that are not expected to traverse the pore and smaller pseudohalides that both traverse the CFTR pore and are thiol reactive (Ag(CN) 2 and Au(CN) 2 ).…”
Section: Pore-lining Tmsmentioning
confidence: 99%
“…In some cases (see Fig. 4), patches were subsequently treated with 2 mM sodium pyrophosphate (PP i ) to stabilize the channel open state (27,28), as described previously in studies of state-dependent modification of Cys-less CFTR (8,15). Both intracellular (bath) and extracellular (pipette) solutions contained (in mM): 150 NaCl, 2 MgCl 2 , 10 N-tris[hydroxymethyl]methyl-2-aminoethanesulfonate, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate potential Cd 2ϩ bridges formed between porelining cysteine side chains exposed in the inner vestibule of the CFTR pore, we combined individual cysteines that we previously found to be accessible to cytoplasmically applied methanethiosulfonate reagents in three important pore-lining TMs: TM1 (K95C, Q98C) (13), TM6 (I344C, V345C, M348C, A349C) (15), and TM12 (M1140C, S1141C, T1142C, Q1144C, W1145C, V1147C, N1148C) (16), to generate a total of 50 double cysteine mutants (8 TM1:TM6; 14 TM1:TM12; 28 TM6:TM12).…”
Section: Methodsmentioning
confidence: 99%
“…61 However, other studies argue that the gate might occupy a more cytoplasmic location within the CFTR pore. 62 Identifying the location of this gate is crucial to understand the CFTR gating pathway, the sequence of conformation changes initiated by ATP binding to the NBDs that lead to Cl -flow through the CFTR pore. In turn, this knowledge as well as information about the architecture of the CFTR pore is vital to understand the mechanism of action of smallmolecule CFTR modulators.…”
Section: 41mentioning
confidence: 99%